Effects of delayed appointments in fixed orthodontic patients due to lockdown during the COVID-19 pandemic - Vinay Kumar Chugh; Navleen Kaur Bhatia; Pravin Kumar; Ankita Chugh; Surjit Singh; Sam Prasanth Shankar; Priyawati Moungkhom; Rinkle Sardana (Journal of Oral Biology and Craniofacial Research)
Objectives: To determine the frequency of orthodontic emergencies and their impact on the treatment progress caused by delayed appointments due to the lockdown during the COVID-19 pandemic. Materials and methods: Two hundred thirty-eight patients undergoing fixed orthodontic treatment participated in this cross-sectional study. A pre-structured questionnaire was divided into six parts (Part A-C comprised of orthodontic emergencies and Part D-F comprised of various adverse effects and impacts on treatment progress). Two specialist orthodontists performed clinical examinations to complete the questionnaire. The final data were expressed as frequency and percentage. Results: Maximum number of patients reported four months after lockdown. Nearly half of the patients reported debonding of at least one of the brackets. Loosening of molar bands and debonding of second molar tubes were observed in 12.6% and 18.9% of patients, respectively. Ligation method failures were reported in 41.2% of the patients. Patients fitted with transpalatal arch/lingual arch skeletal anchorage showed a failure rate of 26.1% and 10%, respectively. Almost 29% of the patient complained of discomfort due to distal wire impingement. Undesired tooth movements were seen in almost 25% of patients. Alignment, space closure, and settling of occlusion were affected in 47.6%, 17.4%, and 35.7% of patients, respectively. Conclusions: This study helps to determine various types of adverse effects that can occur due to delayed appointments. The study's outcomes suggest that clinicians should be prepared to deal with future pandemics or other causes that might lead to delayed appointments.